Spin fluctuations yield zT enhancement in ferromagnets - Md Mobarak Hossain Polash (Elsevier, 2021)
Summary: Thermal fluctuation of local magnetization intercoupled with charge carriers and phonons offers a path to enhance thermoelectric performance. Thermopower enhancement by spin fluctuations (SF) has been observed before. However, the crucial evidence for enhancing thermoelectric-figure-of-merit (zT) by SF has not been reported until now. Here we report that the SF leads to nearly 80% zT enhancement in ferromagnetic CrTe near and below TC ∼ 335 K. The ferromagnetism is originated from the collective electronic and localized magnetic moments. The field-dependent transport properties demonstrate the profound impact of SF on the electrons and phonons. Under an external magnetic field, the enhancement in thermopower is suppressed, and the thermal conductivity is enhanced, evidencing the existence of a strong SF. The anomalous thermoelectric transport properties are analyzed based on theoretical models, and a good agreement with experimental data is found. This study contributes to the fundamental understanding of SF for designing high-performance spin-driven thermoelectrics.